Structural and physical properties of Nd-doped Pb(Zr0.52Ti0.48)O3ceramics - W. Thamjaree (2018)
Lead zirconate titanate (PZT) ceramics (Zr/Ti = 52/48) have been modified with different quantities of neodymium oxide (Nd2O3). The preparation was carried out via the solid-state-reaction route. The samples were calcined and sintered at 850°C and 1200°C, respectively. The structural evolution and the microstructure were investigated using an X-ray diffractometer (XRD) and a scanning electron microscope (SEM), respectively. The physical properties such as dielectric constants, piezoelectric coefficients, density etc. were also studied. Copyright © Taylor & Francis, Inc.